Synthesis and Characterization of Pt‐loaded Carbon Nanostructures Derived from Polyaniline Nanotubes - Xu, Gong‐Da; Kim, Pil; Lee, Youn‐Sik (Bulletin of the Korean Chemical Society, 2017)
KCI Citation Count: 1